2020
DOI: 10.1002/tsm2.135
|View full text |Cite
|
Sign up to set email alerts
|

Effects of deceptive footwear condition on subjective comfort and running biomechanics

Abstract: Comfort is a major criterion for footwear selection. Previous studies have suggested that physical properties were not enough to predict comfort and psychological factors could also affect the perception. To understand comfort, this study examined the effect of controlled shoe description and price cue on the perception of comfort. Furthermore, this study also examined the running biomechanics in response to footwear conditions of differing comfort. Fifteen runners completed treadmill running tests in two cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 26 publications
(47 reference statements)
0
10
0
Order By: Relevance
“…Third, the participants were reminded about the foot insole conditions prior to the landing tasks. We expected that our participants would favor their positive expectation to the functional benefits of footwear and thus result in greater changes in actual performances, as described in previous studies [28,47]. Mohr et al [27] reported that lightweight shoes leads to significantly better jump and shuffle cut performances than heavy shoes only when the participants were informed about the shoe mass differences (related to mechanical energy).…”
Section: Discussionmentioning
confidence: 71%
See 3 more Smart Citations
“…Third, the participants were reminded about the foot insole conditions prior to the landing tasks. We expected that our participants would favor their positive expectation to the functional benefits of footwear and thus result in greater changes in actual performances, as described in previous studies [28,47]. Mohr et al [27] reported that lightweight shoes leads to significantly better jump and shuffle cut performances than heavy shoes only when the participants were informed about the shoe mass differences (related to mechanical energy).…”
Section: Discussionmentioning
confidence: 71%
“…Since the comfort level of footwear is considered to be a non-invasive and reliable measure of the potential risk of sports injuries, the relationship of psycho-motor effect requires further evaluation. One plausible explanation of Red-AS benefits is that psychological factors including the awareness and confidence in the benefits of footwear modification would maximize the influence of actual sports performances [26][27][28]. Another plausible mechanism is that visual/color perception would play some role in regulating the degree of comfort perception and movement control [33,58].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Three studies explored the effects of perceptual factors on footwear comfort. Chamb et al [ 30 ] evaluated running biomechanics on a treadmill under two footwear conditions (shoe A and B). Identical running shoes were used in both conditions, but shoe B was described to be the “latest model designed to maximize comfort” and more expensive than shoe A.…”
Section: Resultsmentioning
confidence: 99%